Modifications Implemented to the Chemistry laboratories due the COVID-19 Pandemic at the International and National level, the Case of the National University and the University of Costa Rica in 2020–2021 and their Successes or Deficiencies - Corrales González, Yorleni (2023)
This essay addresses the problems faced by chemistry laboratory teachers during the COVID-19 pandemic, the contingency measures used to continue virtual laboratory courses, such as online chemical simulators and the application of home laboratory practices, the recommendations made by experts, as well as some impressions of the student body regarding the measures implemented by their teachers. In addition, some measures taken by two state universities from Costa Rica to deal with this anomalous situation are discussed. Although the studies consulted agree that virtuality loses the essence of a laboratory course, as there is no possibility of handling equipment and instrumentation, it is considered that the use of virtual and technological tools is a good complement to support the learning of students and that their inclusion is important for the development of education in the chemistry laboratory.